2012
DOI: 10.1016/j.jvs.2012.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Supervised walking therapy in patients with intermittent claudication

Abstract: SWT is effective in improving MWD and PFWD in patients with IC. However, pooled results from the RCTs did not identify any of the exercise components including intensity, duration, or content of the program as being independently associated with improvements in MWD or PFWD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 49 publications
3
107
0
4
Order By: Relevance
“…37 There is uncertainty about the optimal duration of SET resulting in maximally improved walking distances. 38 Previous research on optimal length of SET programs has found the greatest improvement in walking distance during the first 2 months of therapy, 39 which is in accordance with our findings. Both groups of the present study received a similar number of training sessions and were engaged in a similar amount of treadmill walking.…”
Section: Discussionsupporting
confidence: 92%
“…37 There is uncertainty about the optimal duration of SET resulting in maximally improved walking distances. 38 Previous research on optimal length of SET programs has found the greatest improvement in walking distance during the first 2 months of therapy, 39 which is in accordance with our findings. Both groups of the present study received a similar number of training sessions and were engaged in a similar amount of treadmill walking.…”
Section: Discussionsupporting
confidence: 92%
“…In general, a 50e200% improvement of ACD has been reported. 19 Besides, as walking on the ground requires higher ground reaction forces and movement power compared with treadmill walking, 20 it may also be possible that an increase in treadmill based walking distance of approximately 100 m is insufficient to reveal any effect on walking distance in daily life. These findings might suggest that SET should not only be focused on treadmill walking, but should additionally include outdoor walking and strength training.…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, among the exercise therapies available, supervised exercise therapy (SET), which is programmed training under the supervision of trained physiotherapists or doctors, has been demonstrated to provide better results than non-interventional exercise. 13 However, a large, randomized controlled trial for patients with IC and superficial femoral arterial disease that compared SET with EVT or combined treatment (EVT plus SET) found no difference among the groups after 1 year of intervention. 14 Considering the cost of EVT (using stents) and the risk of operative complications, including incidental occlusion of collateral vessels, which would exacerbate ischemia, the ideal treatment strategy for patients with IC seems to be SET plus best medical treatment (BMT) rather than EVT, at present.…”
Section: Utilization Of Oxidative Stress Biomarkers Is Important To Amentioning
confidence: 99%